Bioflavonoid exerts analgesic and anti-inflammatory effects via transient receptor potential 1 channel in a rat model - Zarei, Mohammad Mahdi; Abdolmaleki, Zohreh; Shahidi, Siamak (Arquivos de Neuro-Psiquiatria, 2022)
Background Pain is an uncomfortable sensation in the body. Kaempferol is a flavonoid with antinociceptive effects. Transient receptor potential (TRP) channels have been characterized in the sensory system.Objective This study evaluated the central antinociceptive effect of Kaempferol and possible mechanisms of action of transient receptor potential cation channel subfamily V member 1 (TRPV1).Methods Capsaicin as a TRPV agonist (5 μg/μL, intracerebroventricular [ICV]) and capsazepine as its antagonist (10 μg/μL, icv) were used to test the analgesic effect of kaempferol (1.5 mg, ICV). Morphine (10 μg, ICV) was used as a positive control. The other groups were treated with a combination of kaempferol and capsaicin, kaempferol and capsazepine, and capsaicin and capsazepine. The cannula was implanted in the cerebroventricular area. The tail-flick, acetic acid, and formalin tests were used to assess analgesic activity. For evaluation of antiinflammatory effect, the formalin-induced rat paw edema was used.Results Kaempferol significantly decreased pain in the acute pain models, including the tail-flick and the first phase of the formalin test. In the late phase of the formalin test, as a valid model of nociception, capsazepine inhibited the antinociceptive effect of kaempferol.Conclusions Kaempferol has an analgesic effect in the acute pain model and can affect inflammatory pain. Also, the TRPV1 channel plays a role in the antinociceptive activity of kaempferol.
Keywords: Analgesia; TRPA1 Cation Channel; Rats; Flavonoids